Effect of Rubber Dam Clamps on Demineralized Cervical Enamel of Permanent Teeth - Bosco Mendes, Ana Carolina [UNESP]; Restrepo, Manuel; Rizzato Azevedo, Elcilaine [UNESP]; Loiola Cordeiro, Rite De Cassia [UNESP]; Santos-Pinto, Lourdes [UNESP]; Cilense Zuanon, Angela Cristina [UNESP] (Amer Soc Dentistry Child, 2018)
Purpose: To evaluate the effect of two molar clamps on artificially demineralized enamel of permanent teeth after three periods of isolation. Methods: Twenty extracted third molars were immersed in a biological solution for development of artificial white spot lesions and then were equally divided into two groups according to the clamp being placed (Group G205: clamp no. 205; Group G26: clamp no. 26). The loss of fluorescence and lesion area of demineralized surface after each isolation were assessed by quantitative light-induced fluorescence. Results: There were significant statistical differences in artificially induced white spot lesions after the second and third clamp placement with both damps. There was also a significant difference in quantitative light-induced fluorescence readings between groups when molar damps were placed for the third time. Conclusion: It is possible to lose dental structure when using rubber dam clamps on teeth with white spot lesions in the cervical enamel.
Keywords: DEMINERALIZATION; DENTAL CARIES; RUBBER DAM